PENGARUH MODEL PEMBELAJARAN STUDENT FACILITATOR ANDEXPLAINING BERBANTUAN MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR DAN AKTIVITAS SISWA MATERI IKATAN KIMIA DI SMA - Yurmida Yurmida; Rachmat Sahputra; A Ifriany Harun (Universitas Tanjungpura, 2019)
AbstractThis research aimed to know the influence of learning models Student Facilitator and Explaining (SFE) a media-assisted learning towards student learning outcomes and activities on chemical bonding material in class X SMAN 2 Sungai Kakap. Form of research was quasy experimental with Nonequivalent Control Group Design.This form of research was research used experiment with this type of design used control group pretest posttest design.The population in this research was the whole grade X SMAN 2 Sungai Kakap. The technique of sampling was saturated sampling.Class X MIA I as class experiments and MIA X 2 as a control class. Data collection was performed with the measurement techniques, the techniques of direct communication, and direct observation technique.Data collecting instrument that was used in the form of test results of study essay and non-shaped test student activity sheet-shaped..The results of observation of the activity of the students class experiments showed that more active than the control class. Based on the results of the statistical tests using test U-Mann Whitney with α = 5%, there was a significant difference between the results of the experimental class students and grade control. Learning model-assisted learning media SFE giving the influence of 20.88% against student learning results on chemical bonding material in class X SMAN 2 Sungai Kakap with a price effect size 0.50. Keywords:Activities, Chemical Bonds, Learning Outcomes,Student Facilitator and Explaining